2012
DOI: 10.4067/s0718-95162012000200001
|View full text |Cite
|
Sign up to set email alerts
|

Water management for wheat grown in sandy soil under climate change conditions

Abstract: The effect of fertigation regimes on wheat grown in sandy soil was tested in two field experiments in Egypt. The aim of the study was to determine the vulnerability of wheat to extreme weather event under climate change scenarios. Eight fertigation treatments, in addition to farmer irrigation were tested. Two climate change scenarios obtained from Hadley climate change model were incorporated in CropSyst model to assess wheat yield responses to fertigation regimes under these scenarios. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…It was reported that the CropSyst model was appropriate in predicting growth and yield of wheat under different irrigation treatments, where the value of RMSE was 0.36 ton ha −1 and the RMSE value between observed and predicted biomass was 1.27 ton ha −1 [39]. Similar results were obtained with a low RMSE value and higher d-stat value [36,40,41]. within the same column for each trait with the same lower-case letter are not significantly different according to Tukey's HSD (honestly significant difference) test at p ≤ 0.05.…”
Section: Cropsyst Validationsupporting
confidence: 67%
“…It was reported that the CropSyst model was appropriate in predicting growth and yield of wheat under different irrigation treatments, where the value of RMSE was 0.36 ton ha −1 and the RMSE value between observed and predicted biomass was 1.27 ton ha −1 [39]. Similar results were obtained with a low RMSE value and higher d-stat value [36,40,41]. within the same column for each trait with the same lower-case letter are not significantly different according to Tukey's HSD (honestly significant difference) test at p ≤ 0.05.…”
Section: Cropsyst Validationsupporting
confidence: 67%
“…These results indicating that, water stress ( I 3 ) had more adverse effect on relative water content, transpiration rate, plant height, number of spikes/m 2 , number of grains/spike, its may be due to the effect of water deficit on pollinated and fertilization processes, then caused decreasing that traits and then decreased 1000-grain weight and grain yield. The previous results are in full agreement with those reported by Abd El-Gawad et al (1998) andEl Far &Teama (1999), Siddique et al (2000) , El-Sayed (2003, Hefnawy & Wahba (2003), Huang GuanHua et al (2008), Lui HaiJun et al (2011, Sayed &Bedaiwy (2011) and Ibrahim et al (2012) Cultivar differences effect Data given in Table 6 clearly indicate the significant differences among wheat cultivars respecting number of grains/spike, 1000-grain weight(g) and grain yield ardab/fed in the two seasons and their combined. The highest value of number of grains/spike in combined data was obtained by Giza 168 (41.03) followed by Sids 12 (39.11) and Gemmeiza 11 (32.77), whereas, Sakha 94 showed lowest value (28.43).…”
Section: Interaction Effectsupporting
confidence: 90%
“…While irrigation with a depth over 1.0E also had negative effect on 1000-grains weight and yield. Ibrahim, et al (2012) found that, irrigating wheat grown in sandy soil with an amount of either 1.0 or 0.8 of ETc with fertigation application in 80% of application time is recommended to enhance growth and yield, and to reduce wheat's damage caused by extreme climate change.…”
mentioning
confidence: 99%
“…These points can be spent on almost 44 different food products and used from 27,000 partnered private grocery stores and 5,000 state-owned consumer complexes. The government bears costs of about EGP 5.4 Billion (306$ million) annually on this point system (19,32).…”
Section: A Wheat In Egyptmentioning
confidence: 99%
“…It is very important to get safe food without endangering any other civilians. Moreover, consumer's preferences can be an issue if the food price does not fit with the PPP and national income, therefore, Egypt suffers a huge crisis in food and the most imported grain that causes deficits in the country dollar reserves is wheat (13,19,20,23).…”
Section: B Factors Affecting Wheatmentioning
confidence: 99%